The History of the Communist Party of Great Britain Volume 1 : 1919-1924 Formation and Early Years - Klugmann, James (Book collections on Project MUSE., 2015)
This first in the six volume series covers the early 20s - the wave of post-war militancy, the negotiations between Marxist groups which led to the formation of the Communist Party, the Party's early organisation and political policies, and the coming into office and the fall of the First Labour Government.